Penerapan Teori Caring Jean Watson pada Ibu Hamil Gemelli dengan BB Janin Kurang - Reni Andriyani; Irna Nursanti (Journal of Telenursing (JOTING), 2025)
This study aims to explain the application of Jean Watson's Caring Theory in nursing care for pregnant women with twins with low birth weight and umbilical cord blood flow disorders and to assess its impact on the client's physical and psychological condition. The research method used a case study with a nursing process approach based on Jean Watson's theory. The results showed that the application of Watson's ten carative factors resulted in significant improvements in maternal nutritional status, fetal stabilization, and decreased anxiety. Meal portions increased, weight gain improved, and fetal heart rate stabilized based on monitoring. Anxiety levels decreased, as evidenced by more open expression of feelings and lower anxiety scores. Therapeutic relationships and spiritual support played a significant role in increasing the client's calm and motivation. In conclusion, Jean Watson's Caring Theory is effective for high-risk pregnant women, especially in cases with a combination of biophysical and psychological problems. The caring approach helps improve the mother's physical condition, stabilize the fetus, and reduce anxiety through a therapeutic relationship and emotional and spiritual support. These findings confirm that integrating Watson's theory with Indonesian nursing standards can improve the quality of maternity nursing care.   Keywords: Nursing Care, Jean Watson's Caring, Pregnant Women, Carative